The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1984
DOI: 10.1037/0096-1523.10.6.749
|View full text |Cite
|
Sign up to set email alerts
|

Shape and depth perception from parallel projections of three-dimensional motion.

Abstract: Parallel projections of dots on the surface of a transparent sphere rotating about a vertical axis provide strong impressions of depth and spherical shape. The hypothesis was tested that these impressions are the result of three perceptual heuristics: (a) The sinusoidal projected velocity function of each dot in the horizontal dimension tends to be perceived as a rotary motion in depth; (b) the projected velocity gradient in the vertical dimension is perceived as curvature in depth; and (c) the simultaneously … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
45
0

Year Published

1988
1988
2005
2005

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 11 publications
1
45
0
Order By: Relevance
“…Wallach and O'Connell (1953) demonstrated that if subjects are shown the two-dimensional (2-D) shadow cast by a clear glass sphere that has small opaque dots on its surface and rotates about a vertical axis, then subjects perceive a spherical surface. A similar perception is commonly reported for computer-generated displays in which dots move about on a computer screen in a manner consistent with their being projections of dots on a rotating sphere (see, e.g., Braunstein, 1966;Braunstein & Andersen, 1984). Apparently human vision is adept at inferring 3-D structure from the 2-D motions of projected features.…”
mentioning
confidence: 68%
“…Wallach and O'Connell (1953) demonstrated that if subjects are shown the two-dimensional (2-D) shadow cast by a clear glass sphere that has small opaque dots on its surface and rotates about a vertical axis, then subjects perceive a spherical surface. A similar perception is commonly reported for computer-generated displays in which dots move about on a computer screen in a manner consistent with their being projections of dots on a rotating sphere (see, e.g., Braunstein, 1966;Braunstein & Andersen, 1984). Apparently human vision is adept at inferring 3-D structure from the 2-D motions of projected features.…”
mentioning
confidence: 68%
“…The organization of texture elements along meridian lines does reduce the heterogeneity of velocities. Such reductions have been found to reduce the perceived depth in kinetic depth effect displays (Braunstein & Andersen, 1984). However, all observers reported perceiving the stimuli as spheres in the y-axis conditions (some perceived the z-axis stimuli as disks).…”
Section: Notementioning
confidence: 90%
“…Sperling et al (1989) used a fInite set of 53 different 3-D shapes in a shape identifIcation task, but did not report quantitative differences in performance for different 3-D shapes. Braunstein and Andersen (1984) noted that spheres, for example, might have certain heuristic topological characteristics that would make them special objects, not suitable for a generalization to other 3-D objects. It has to be examined yet what exactly these "heuristic" properties are.…”
mentioning
confidence: 99%